Ghana : Corporatization of Distribution Concessions through Capitalization - World Bank (Washington, DC, 2014)
This study looks at the potential for using employee stock ownership plans (ESOPs) as a means of allowing employees of state-owned enterprises to obtain an ownership stake in the privatization of electricity distribution concessions. Privatization programs worldwide are increasingly including a focus on incorporating an element of employee ownership in order to ensure that ownership of the privatized enterprises will be shared broadly by its workers, not just wealthy investors. This study looks at the relevant international experience and offers guidelines for introducing appropriate legal reforms that could facilitate the implementation of employee ownership as a key element of the government's privatization strategy.